Therapeutic metamorphosis: Findings from a grounded theory study of the impact of low‐dose prophylaxis in children living with haemophilia in India. Issue 4 (12th June 2020) - T, Rohini; Thomas, Gino; Paul, Linny; Mathew, Sheena; Biss, Tina; Hanley, John P.; Narayana Pillai, Vijayakumar
Abstract: Introduction: The clinical benefits of administering low‐dose prophylaxis in children with haemophilia are well established. Qualitative research describing the impact of prophylaxis on quality of life is comparatively rare in this area. Aim: The aim of this study was to investigate in children the experiences of living and becoming adjusted to haemophilia before prophylaxis, by collecting information directly from children and their parents or guardians. A further goal was to evaluate whether and how the use of low‐dose prophylaxis impacts the disease experience. Methods: A grounded theory design according to Strauss and Corbin was chosen for this study. The study was conducted in the Haemophilia Treatment Centre at Aluva, Kerala, India and involved nineteen participants (children, mothers, father and grandmothers) who were selected by theoretical sampling. Data were collected through audiotaped interviews, which included demographic and semi‐structured interview questions. Data were coded and evolved into concepts and categories that lead to the emergence of theory. Results: The study resulted in the construction of 'Theory of Therapeutic Metamorphosis'. It comprised two stages: stage of bondage (enduring hardships), experienced during the absence of prophylaxis or on‐demand treatment and stage of freedom (deliverance/reductions, energized life/improvements and behaviour to seek prophylaxis) experienced during low‐dose prophylaxis. Conclusion: This study illustrates the challenges faced by children with haemophilia and their families and the positive impact of low‐dose prophylaxis. Further prospective research studies are required to add to the growing knowledge in this area.